ANALYSIS OF DINAMIC MODEL FOR THE INFLUENCE OF INFLUENCER AND FOLLOWERS ON SOCIAL MEDIA - Caterine Siregar, Stephanie
Influencer is a new phenomenon in this era of social media where business owner can pay internet celebrities with various kind of popularity to upload something on their social media accounts to reach potential followers. This phenomenon is one of marketing strategy. Influencers can influence followers’ decision because of their authority, knowledge, position, or level of the engagement. These followers are usually obtained by influencers by sharing their thoughts or reviews on something on social media. Not only as a marketing tool, influencers can even guide people in decision making. This final project will discuss the phenomenon of influencers in Indonesia. The spread of influencers is modeled on the basis of the Susceptible, Infectible, and Recovered (SIR) model. Then we will look for the equilibrium point of the model and analyze its stability. Numerical simulation will be carried out to see how the effect of changes in the values of several parameters on the dynamics model that has been built. From the numerical simulation, it is found that the interaction factor that occurs between influencers and followers is very influential on the phenomenon of population growth of followers and influencers.